2023
DOI: 10.1017/cts.2023.648
|View full text |Cite
|
Sign up to set email alerts
|

What is well-being? A scoping review of the conceptual and operational definitions of occupational well-being

Tara G. Bautista,
Gretchen Roman,
Munziba Khan
et al.

Abstract: Well-being is a multifaceted construct that is used across disciplines to portray a state of wellness, health, and happiness. While aspects of well-being seem universal, how it is depicted in the literature has substantial variation. The aim of this scoping review was to identify conceptual and operational definitions of well-being within the field of occupational health. Broad search terms were used related to well-being and scale/assessment. Inclusion criteria were (1) peerreviewed articles, (2) published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…Finally, we included two manuscripts that guide the clinical and translational science community in approaching future research in well-being. The scoping review by Bautista et al [8] aimed to explore conceptual and operational definitions of well-being within occupational health. Conducted through a broad search using terms related to well-being and scale/assessment, the study identified 388 peer-reviewed articles meeting inclusion criteria.…”
mentioning
confidence: 99%
“…Finally, we included two manuscripts that guide the clinical and translational science community in approaching future research in well-being. The scoping review by Bautista et al [8] aimed to explore conceptual and operational definitions of well-being within occupational health. Conducted through a broad search using terms related to well-being and scale/assessment, the study identified 388 peer-reviewed articles meeting inclusion criteria.…”
mentioning
confidence: 99%